2021
DOI: 10.1177/0950017021997369
|View full text |Cite
|
Sign up to set email alerts
|

Lordly Management and its Discontents: ‘Human Resource Management’ in Pakistan

Abstract: New institutionalism increasingly informs work on comparative human resource management (HRM), downplaying power and how competing logics play out, and potentially providing an incomplete explanation of how and why ‘HRM’ and associated practices vary in different national contexts. We examine HRM in Pakistan’s banking industry and assess how managers’ espoused views of HRM practices reflect prevailing ones in dominant HRM models, and how they differ from early-career professionals’ perceptions of these practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 64 publications
5
21
1
Order By: Relevance
“…Paternalism additionally prompts huge status contrasts among managers and those they deal with that add up to more than formal lines of power. Saqib et al (2021) found that early-career employees thought top directors were far off from them, neglecting to communicate with them enough and understand their jobs. High-status chiefs or managers and their top picks (i.e., favorites) will more often display an authoritarian-paternalism, with a solid penchant for entitlement, whereas subordinates possess little power and are expected to be "kow-towers or ladies" to the seth (Nizami et al, 2017;Saini & Budhwar, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Paternalism additionally prompts huge status contrasts among managers and those they deal with that add up to more than formal lines of power. Saqib et al (2021) found that early-career employees thought top directors were far off from them, neglecting to communicate with them enough and understand their jobs. High-status chiefs or managers and their top picks (i.e., favorites) will more often display an authoritarian-paternalism, with a solid penchant for entitlement, whereas subordinates possess little power and are expected to be "kow-towers or ladies" to the seth (Nizami et al, 2017;Saini & Budhwar, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is possibly not the deficiency of skills and knowledge for implementing an well-organized corporate culture, but a different mind-set of owning businesses, assets, and human resources that serves as a hurdle to the much-required change (Mukhtar, 2021). In academic literature, this "seth approach" is characterized as "seth-leadership" (Khakwani & Case, 2012) and "lordly-management" (Saqib et al, 2021). Saqib et al (2021) argued that the cultural characteristics of "seth" (a neofeudalist authority) affects the managerial application of HRM policies and contests the advocated HRM logic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organizations in Pakistan have hybrid management practices in that they display signs of modernity while simultaneously preserve a traditional (seth) manner of managing employees (Khakwani and Case, 2012). In the Pakistani context, Saqib et al (2022) showed that though management may intend to enact well-being oriented HRM practices, but the same HR practices become a manifestation of culturally appropriate "lordly management style (seth management in Urdu)" when enacted by line managers; these lordly management practices (in the guise of HRM practices) neglect employee well-being and "reinforce and accentuate existing material and status differences"(p.14) between management and employees. HRM practices may be designed with the best of intentions by the HRM department; however, "By maintaining seth culture, managers are able to reproduce their social power and status, disrupting and negating the aims of HRM in dominant HRM models" (Saqib et al, 2022).…”
Section: Practical and Contextual Implicationsmentioning
confidence: 99%